Ongoing barriers to immediate postpartum long-acting reversible contraception: a physician survey - Emily C. Holden; Erica Lai; Sara S. Morelli; Donald Alderson; Jay Schulkin; Neko M. Castleberry; Peter G. McGovern (BMC, 2018)
Abstract Background Postpartum women are at risk for unintended pregnancy. Access to immediate long-acting reversible contraception (LARC) may help decrease this risk, but it is unclear how many providers in the United States routinely offer this to their patients and what obstacles they face. Our primary objective was to determine the proportion of United States obstetric providers that offer immediate postpartum LARC to their obstetric patients. Methods We surveyed practicing Fellows and Junior Fellows of the American College of Obstetricians and Gynecologists (ACOG) about their use of immediate postpartum LARC. These members are demographically representative of ACOG members as a whole and represent all of the ACOG districts. Half of these Fellows were also part of the Collaborative Ambulatory Research Network (CARN), a group of ACOG members who voluntarily participate in research. We asked about their experience with and barriers to immediate placement of intrauterine devices and contraceptive implants after delivery. Results There were a total of 108 out of 600 responses (18%). Participants practiced in a total of 36 states and/or US territories and their median age was 52 years. Only 26.9% of providers surveyed offered their patients immediate postpartum LARC, and of these providers, 60.7% work in a university-based practice. There was a statistically significant association between offering immediate postpartum LARC and practice type, with the majority of providers working at a university-based practice (p < 0.001). Multiple obstacles were identified, including cost or reimbursement, device availability, and provider training on device placement in the immediate postpartum period. Conclusion The majority of obstetricians surveyed do not offer immediate postpartum long-acting reversible contraception to patients in the United States. This is secondary to multiple obstacles faced by providers.